Fenómenos Migratórios e Processos de Construção Identitária Uma leitura antropológico-filosófica - Fitas, Ana Paula (Trabalhos de Antropologia e Etnologia, 2020)
This article focuses on the construction of identity processes in contexts marked by migratory phenomena. Considering that the processes of human mobility imply adaptation mechanisms and cultural resistance inherent to the processes of social change, it is intended, with this reflection, to highlight the relationship of these processes with the state of anomie that sustains them socially with repercussions in the emergence of representations and identity affirmations of its protagonists, from the departure of their countries of origin, to the migratory journey and to the process of establishment in the host societies.